Fatigue optimization of rotary control head rubber core based on steady sealing. (February 2022) - Guo, Lianglin; Zeng, Yijin; Huang, Jian; Wang, Zhiliang; Li, Junxiong; Han, Xueying; Xia, Chengyu; Qian, Liqin
Highlights: The fatigue optimization of the rubber core should meet its sealing requirements. Yeoh model fits well with the uniaxial compression test data of the rubber. Taguchi method combined with numerical simulation is used to optimize rubber cores. The applicable working conditions are selected to reduce the risk of blowout. The performance of the optimized rubber cores is evaluated in field applications. Abstract: In the process of underbalanced pressure drilling, the drill pipe body and its joint repeatedly pass though the sealing rubber core of the rotating blowout preventer (RBOP), making the rubber core susceptible to alternating cyclic load, and prone to fatigue failure. Under the premise of effective sealing realized by the rubber core, to increase its service life, first the Yeoh constitutive model and constitutive parameters describing the material of rubber core were determined by uniaxial tensile and compression tests, and the finite element governing equation of the nonlinear large deformation of the rubber core was obtained according to the principle of virtual work; then a three-dimensional finite element model of the rubber core was established by ABAQUS software to simulate the dynamic sealing process, contact pressure and Mises stress distribution and variation on the sealing surface were analyzed, and the accuracy of the finite element analysis results was verified by comparing the existing test results; subsequently, the influence of structural parameters such as inner angle, outer angle and inner diameter on the sealing surface stress was studied, and these parameters were optimized through Taguchi experiment. The optimal combination of structural parameters was obtained as inner angle 29°, outer angle 69° and inner diameter 84 mm. The maximum Mises stress was reduced by 2.48 MPa and the Mises stress amplitude by 42% after optimization. Finally, the suitable conditions of the optimized rubber core were selected based on the applicability analysis to conduct the field application and result shows that the rubber core has good sealing performance and significantly increased fatigue life after optimization.